Genetic association between STAT4 and primary Sjögren’s syndrome in Han Chinese women - Fangfang Li; Fangfang Li; Junhui Lu; Chao Cen; Wanqiu Zhen; Jiaojiao Zhang; Shengming Wang; Shengming Wang (Frontiers in Genetics)
IntroductionSTAT4, a pivotal transcription factor governing immune and inflammatory responses, has been implicated in autoimmune pathogenesis. This case-control study aimed to examine the relationship between STAT4 single-nucleotide polymorphisms (SNPs) and primary Sjögren’s syndrome (pSS) in a female Chinese Han population, exploring potential genetic mechanisms underlying pSS susceptibility.MethodsSix STAT4 single-nucleotide polymorphisms (rs10931481, rs1400656, rs10168266, rs3821236, rs7601754, and rs10174238) were genotyped using MassARRAY, with STAT4 expression determined by quantitative real-time PCR and cytokine levels assessed via ELISA.ResultsThe rs10168266-C allele emerged as a significant risk factor for pSS, with CC homozygotes exhibiting elevated disease susceptibility compared to CT/TT carriers (Pc = 0.001, OR = 1.905). Conversely, the T allele conferred protection (Pc = 0.002, OR = 0.575), and CT genotypes were underrepresented in patients (Pc = 0.003, OR = 0.539). Notably, rs10168266-CC individuals displayed elevated STAT4 expression in peripheral blood mononuclear cells and elevated serum IL-6 levels compared to T allele carriers (both P < 0.05).DiscussionThis study represents the initial investigation to uncover the genetic association between the STAT4 gene and pSS in Han Chinese women. The rs10168266 polymorphism in the STAT4 gene is a novel genetic determinant of pSS susceptibility in female Chinese Han populations. The mechanism may involve dysregulation of IL-6 signaling driven by STAT4, offering a theoretical foundation for the advancement of gene therapy.